A novel steel lever viscoelastic wall with amplified damper force-friction for wind and seismic resistance. (1st May 2020) - Chou, Chung-Che; Tseng, Wen-Hao; Huang, Chun-Hsiang; Tsuang, Steven; Chang, Luh-Maan; Chen, Yung-Hsiang
Highlights: A lever viscoelastic wall (LVEW) that has VE and friction dampers in a device was proposed. The LVEW amplifies the frame lateral displacement and damper force to the frame structure. Three full-scale wall specimens were tested to validate the cyclic response. An iterative procedure was proposed to obtain the displacement amplification for VE dampers. Abstract: This paper presents a new steel wind- and seismic-resisting wall, called a lever viscoelastic wall (LVEW) that includes a velocity-dependent VE damper and a displacement-dependent friction damper in a device, characterized by two different motion phases. In Phase one motion (i.e., small drifts), the VE damper which is activated by a lever delivers amplified lateral force and energy dissipation to the frame structure. In Phase two motion (i.e., medium-to-large drifts), the VE damper is constrained by a stopper and the friction damper, instead, is activated to provide frictional energy dissipation to the frame. The damping is provided by incorporating VE material and sliding friction in a wall configuration, reducing both the wind and earthquake responses of structures in a single unit. The objectives of the work were to (1) develop the force transfer mechanism and kinematics of the LVEW, (2) verify the cyclic response of LVEWs at low and large drifts, and (3) evaluate the limitation of LVEWs for the applications. Three full-scale LVEW specimens were designed and tested to validate the hysteretic response in two motion phases. The hysteretic response of LVEWs obtained from the test was compared to that from the analytical formulation.